POLA HUBUNGAN KERJA SAMA KOLABORATIF ANTARA FARMASIS DAN DOKTER DALAM PELAYANAN KESEHATAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Background: Pharmacist is one of health provider, but the role of pharmacist in health care system is still limited due to the poor relationship between pharmacists and physician in clinical care setting. To deal with this issue, it is important to improve a good collaborative working relationship between physician and pharmacist in health care system. Objectives: The study aims to observe how far the relationship between pharmacist and physician has been implemented in Indonesia and how to develop it. Method: An observation concerning the relationship between pharmacist and physician in Indonesia was carried out using a model of relationship proposed by McDonough and Doucette' as the reference. Results: Most of the pharmacy-physician relationship in Indonesia falls in stage 0 of the model, very few in stage 1 and 2, and none reached stage 4 and 5. The determinant factors are the competency of the pharmacist, the openness of the physicians toward the role of pharmacist in clinical practice, and the policy of the hospital administrator on clinical pharmacy practice. The new regulation is required to optimize the role of pharmacist in health care system. Keywords: pharmacist - physician relationship, clinical pharmacy practice